A picomolar inhibitor of resistant strains of human immunodeficiency virus protease identified by a combinatorial approach - Rinnová, M; Hradilek, M; Barinka, C; Weber, J; Soucek, M; Vondrásek, J; Klimkait, T; Konvalinka, J (Archives of biochemistry and biophysics, 2000)
In order to identify inhibitors of various drug-resistant forms of the human immunodeficiency virus protease (HIV PR), we have designed and synthesized pseudopeptide libraries with a general structure Z-mimetic-Aa1-Aa2-NH2. Five different chemistries for peptide bond replacement have been employed and the resulting five individual sublibraries tested with the HIV PR and its drug-resistant mutants. Each mutant contains amino acid substitutions that have previously been shown to be associated with resistance to protease inhibitors, including Ritonavir, Indinavir, and Saquinavir. We have mapped the subsite preferences of resistant HIV PR species with the aim of selecting a pluripotent pharmaceutical lead. All of the enzyme species in this study manifest clear preference for an L-Glu residue in the P2' position. Slight, but significant, differences in P3' subsite specificity among individual resistant PR species have been documented. We have identified three compounds, combining the most favorable features of the inhibitor array, that exhibit low-nanomolar or picomolar Ki values for all three mutant PR species tested.
Keywords: Drug Resistance; mutace; Combinatorial Chemistry Techniques; Protease Inhibitors; techniky kombinatorické chemie; inhibitory proteas; racionální návrh léčiv; léková rezistence; peptidová knihovna; molekulární modely; Models, Molecular; substrátová specifita; kinetika; Peptide Library; HIV Protease; Substrate Specificity; HIV-proteasa; Drug Design; Mutation; Kinetics